Decreased Reception of Nonverbal Cues in Heroin Addicts - Giannini, A. James; Jones, Brian T. (The journal of psychology, 1985)
The ability to interpret nonverbal cues was tested in 15 young, white American male heroin addicts who were not intoxicated. When their responses were compared with those of age-matched controls, addicts were found to be significantly less accurate in reading nonverbal communications.